In ovo vaccination against Newcastle disease virus using a DNA vaccine co-expressing the F and HN genes and dextran-spermin as a vehicle for DNA delivery - Firouzamandi, Masumeh; Bejo, Mohd Hair; Omar, Abdul Rahman; Mehrbod, Parvaneh; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
Newcastle disease virus (NDV) is recognized as a fatal disease virus affecting domestic and wild avian species. Different types of vaccines are under testing to ensure that there is efficient control. In the present study, a DNA vaccine, namely pIRES-HN/F, alone or in mixture with Dextran-spermine, as a vehicle, was applied for in ovo vaccination to NDV. The antibody titer in the chickens immunised by the pDNA was higher compared to the chickens immunised with pDNA-Dextran complex. The produced antibodies failed to control the acute NDV infection after challenge and the severity of infection in the most of the dead chickens showed variation. Immunisation with the pDNA/Dextran-spermine nanoparticles induced low level of antibody titer compared with the pDNA alone. Therefore, it was concluded that Dextran-spermine was not effective to facilitate the entrance of pDNA into the cell by in ovo vaccination.